2021
DOI: 10.1111/jce.15330
|View full text |Cite
|
Sign up to set email alerts
|

Mortality benefit of catheter ablation versus medical therapy in atrial fibrillation: An RCT only meta‐analysis

Abstract: Introduction Catheter ablation for atrial fibrillation (AF) in comparison to medical therapy alone is known to improve freedom from arrhythmia and quality of life, but the benefit regarding mortality is unclear. The publication of several recent large randomized controlled trials (RCT) comparing ablation with medical therapy has warranted an updated meta‐analysis. Methods We sought to compare the effectiveness of catheter ablation versus medical therapy only in patients with AF. MEDLINE, Cochrane, and http://C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…Findings from aggregate data in meta‐analyses in the general population have shown that AF ablation as compared to conservative management is associated with significantly reduced risk of all‐cause mortality, HF hospitalization, stroke, and greater freedom from atrial arrhythmias 62,63 . Catheter ablation for AF in HFrEF patients has been shown to reduce AF recurrence, mortality, and HF hospitalization 49,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from aggregate data in meta‐analyses in the general population have shown that AF ablation as compared to conservative management is associated with significantly reduced risk of all‐cause mortality, HF hospitalization, stroke, and greater freedom from atrial arrhythmias 62,63 . Catheter ablation for AF in HFrEF patients has been shown to reduce AF recurrence, mortality, and HF hospitalization 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Findings from aggregate data in meta-analyses in the general population have shown that AF ablation as compared to conservative management is associated with significantly reduced risk of all-cause mortality, HF hospitalization, stroke, and greater freedom from atrial arrhythmias. 62,63 Catheter ablation for AF in HFrEF patients has been shown to reduce AF recurrence, mortality, and HF hospitalization. 49,50 In HFpEF patients, catheter ablation compared to medical therapy is significantly associated with reduction in AF recurrence, 64,65 and may be associated with significant benefit in mortality or HF hospitalization.…”
Section: F I U R Ementioning
confidence: 99%
“…8 A recent report showed that catheter ablation for AF resulted in a significant reduction in all-cause mortality and hospitalization, and a greater improvement in left ventricular systolic function than medical therapy. 9 In addition, the Catheter Ablation versus Standard Conventional Therapy in Patients with Left Ventricular Dysfunction and Atrial Fibrillation (CASTLE-AF) trial reported that catheter ablation for AF with heart failure and severe systolic dysfunction (left ventricular ejection fraction [LVEF] ≤35%) was associated with a reduction in mortality or heart failure. 10 However, the clinical outcomes of catheter ablation for AF in heart failure with mid-range ejection fraction (HFmrEF) and preserved ejection fraction (HFpEF) have not been fully evaluated.…”
Section: Study Populationmentioning
confidence: 99%
“…For example, the CABANA (Catheter Ablation vs. Antiarrhythmic Drug Therapy for Atrial Fibrillation) trial reported that CA did not significantly reduce the primary end point of death, disabling stroke, severe bleeding, or cardiac arrest compared with MT [ 9 ]. Several meta-analyses comparing CA vs. MT reported outcomes such as a reduction in all-cause mortality and hospitalizations, improvement in left ventricular ejection fraction (LVEF), and greater freedom from atrial arrhythmia and AF [ 10 ]. However, contrasting evidence on the effectiveness of CAs for these outcomes is available from meta-analyses, and the determination of the credibility of these findings remains to be assessed.…”
Section: Introductionmentioning
confidence: 99%